AUDIT OPERASIONAL ATAS PENGELOLAAN PERSEDIAAN OBAT PADA RUMAH SAKIT UMUM (RSU) AMINAH BLITAR - Jinan, Jeihan Linan (Jurnal Ilmiah Mahasiswa FEB, 2016)
This case study research aims to implement the operational audit in testing the effectiveness of medical inventory management at Aminah Hospital Blitar. The analysis implemented in this study include a preliminary survey, review and testing of Standard Operating Procedures (SOP), and detailed testing. The results of this research showed that recently the hospital has had a clear written inventory management procedures, experienced human resources in the field of hospital’s inventory, and well-organized inventory. However, there are also weaknesses of Aminah’s SOP, such as no rotation of employees in the purchasing department and no practice of internal audit. In addition, this research found irregularities committed by employees in the purchasing department, non disciplined employee in doing stock opname regularly, delay in making the inventory report, and employees negligence in recording inventories. Based on that, it can be concluded that the inventory management  in  Aminah Hospital hasn’t been effective yet and it requires a policy to regulate the employees rotation in the purchasing department, implementing internal audit for the inventories management, and giving strict sanctions against uncompliat employees to the rules of the hospital.   Keywords:  Inventory, Management, Operational Audit, and Effectiveness